Transformation In Urban Design - Abbas, Sana Sati; Tarq, Ahmed Tarq (Iraqi Journal of Architecture and Planning, 2009)
This research deals with the transformation in urban design , as a concept , which has been focused on by the Structuralism, and the Theorist and Designer of Late Post -Modern, for its importance as a Strategy in the Design Process. The concept had been studied in many Disciplines , such as Linguistics , Biology , and Architecture. The Linguistics indicated that each systematic knowledge is composed from basic structure called the Deep Structure . This structure formed the basic rules of transformation, on which the system is stand , this structure is called by ( Chomesky) the Generating rules . Biology showed that the transformation which occurred on form , are external changes and connected with the external form . While the substantial characteristics of the being are fixed during the operation of development and growth. In Architecture , the Literature submitted the types of transformation , which were the transformation in the elements and the transformation in the relationships . Also they submitted some transformation mechanisms , directly or indirectly . Also did the Ethics Literature. The research aims to built a theoretical framework of tansformation, and determine the basic mechanisms used in Architecture and Urban Design. The research reached to five items determined the theoretical framework of the transformation which were , the aim of transformation , the transformation formulas , the types of transformation , the transformation mechanisms, and the behavior of the systems during tle process of transformation.